Early Results of a Phase I Trial Using an Adipose-Derived Mesenchymal Stem Cell-Coated Fistula Plug for the Treatment of Transsphincteric Cryptoglandular Fistulas. Issue 5 (May 2019) - Dozois, Eric J.; Lightner, Amy L.; Mathis, Kellie L.; Chua, Heidi K.; Kelley, Scott R.; Fletcher, Joel G.; Dietz, Allan B.; Friton, Jessica J.; Butler, Greg W.; Faubion, William A.
Abstract : BACKGROUND: Management of transsphincteric cryptoglandular fistulas remains a challenging problem and the optimal surgical approach remains elusive. Mesenchymal stem cells, increasingly being utilized for perianal Crohn's disease, offer a novel therapy to treat cryptoglandular fistulas. OBJECTIVES: This study aimed to determine safety and feasibility of using an autologous mesenchymal stem cell-coated fistula plug in patients with transsphincteric cryptoglandular fistulas. DESIGN: This study is a phase I clinical trial. SETTING: This study was conducted at a tertiary academic medical center. PATIENTS: Adult (>18 years) male and female patients with transsphincteric cryptoglandular fistulas were selected. MAIN OUTCOMES MEASURES: The primary outcomes measured were the safety, feasibility, and efficacy of a mesenchymal stem cell-coated fistula plug in patients with transsphincteric fistulas. RESULTS: Fifteen patients (8 women, mean age 39.8 years) with a single-tract transsphincteric fistula received a mesenchymal stem cell-loaded fistula plug and were followed for 6 months. Duration of disease at the time of study enrollment was a median of 3.0 years (range, 1–13 years) with a median of 3.5 (range, 1–20) prior surgical interventions. Adverse events included 1 plug extrusion, 1 abdominal wall seroma, 3 perianal abscesses requiring drainage, and 1 patient with perianal cellulitis. There were no serious adverse events. At 6 months, 3 patients had complete clinical healing, 8 had partial healing, and 4 patients showed no clinical improvement. Radiographic improvement was seen in 11 of 15 patients. LIMITATIONS: This study was limited by the small cohort and short follow-up. CONCLUSIONS: Autologous mesenchymal stem cell-coated fistula plug treatment of transsphincteric cryptoglandular fistulas was safe and feasible and resulted in complete or partial healing in a majority of patients. See Video Abstract at http://links.lww.com/DCR/A897 .